2017
DOI: 10.1002/per.2119
|View full text |Cite
|
Sign up to set email alerts
|

Open Peer Commentary and Author'S Response

Abstract: Among the topics discussed in the comments, one idea appeared to be supported by most commenters: when personality trait scores are related to possible outcome variables (or possible causal factors, for that matter), scale-level analyses should be supplemented by item-level analyses. This could help to corroborate causal inferences, refine interpretations, rule out measurement/construct overlaps and/or lead to new discoveries. This suggestion is consistent with recent evidence regarding single items often refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 261 publications
(291 reference statements)
0
6
0
Order By: Relevance
“…Given that situations in SJTs are usually only briefly described and thus open to interpretation, these authors suggested that individuals differ in the situation construals they make on the basis of situational cues in SJTs. Furthermore, Brown et al suggested that individual differences in the perception of situational cues in SJTs (i.e., situation construal) might be pivotal for understanding test-takers' responses to SJT items (see also Mussel, Schäpers, Schulz, Schulze, & Krumm, 2017;Schäpers, Mussel et al, 2019).…”
Section: A Closer Look At Situations In Sjtsmentioning
confidence: 99%
“…Given that situations in SJTs are usually only briefly described and thus open to interpretation, these authors suggested that individuals differ in the situation construals they make on the basis of situational cues in SJTs. Furthermore, Brown et al suggested that individual differences in the perception of situational cues in SJTs (i.e., situation construal) might be pivotal for understanding test-takers' responses to SJT items (see also Mussel, Schäpers, Schulz, Schulze, & Krumm, 2017;Schäpers, Mussel et al, 2019).…”
Section: A Closer Look At Situations In Sjtsmentioning
confidence: 99%
“…That is, the ongoing debate on the context-(in)dependency of SJTs has mainly addressed test takers' general domain knowledge (e.g., Lievens & Motowidlo, 2016) and, relatedly, their implicit trait policies (Motowidlo, Hooper, & Jackson, 2006) as well as broad personality dimensions and cognitive ability (Ziegler & Horstmann, 2017). These approaches may be complemented by more fine-grained knowledge about aspects of SJTs that activate these personal attributes.…”
Section: G Ener Al Discussionmentioning
confidence: 99%
“…By observing interindividual differences in expressed agentic behavior (within the relevant exercises), it was then possible to draw conclusions about assessees' assertiveness skill levels. Such assessed individual differences in social skills refer to maximal performance (i.e., what someone is capable of doing when it matters) and should not be equated with individual differences in personality traits (i.e., what someone tends to do in general, typical performance; Breil et al, 2017;Soto et al, in press).…”
Section: Present Researchmentioning
confidence: 99%